The impact of neighbourhood and gap character on seedling recruitment of Trollius europaeus L. and Iris sibirica L. in Molinietum caeruleae meadows - Kostrakiewicz-Gierałt, Kinga (Biodiversity: Research and Conservation, 2013)
The observations were carried out in the years 2007-2010, in the Molinietum caeruleae meadows with different habitat conditions located in Kraków-Kostrze (southern Poland). The greatest number of seedlings of Trollius europaeus and Iris sibirica was recorded in patches dominated by low-statured species with delicate, procumbent stems or small-tussocks. The diminishing of offspring emergence in places prevailed by large-tussocks grasses, as well as in sites overgrown by willows could be a consequence of poor harvesting practices, as well as the stagnation of water in local depressions. Irrespective of patch charracter, the seedling recruitment did not occur in a fully compact plant canopy, the highest number of offspring was observed in gaps without moss and necromass layers, while the greatest abundance of genets was found in openings left after the removal of bryophytes, litter and above ground parts of plants. The decrease in offspring number noted in gaps resulted from the removal of living and died plants combined with top soil raking, which might caused the partial depletion of soil seed bank reserves. Regardless of the patch type, a significantly higher appearance of seedlings of Trollius europaeus and Iris sibirica was found in the largest gaps than in the smallest ones. In light of the performed studies, it might be concluded that gap creating seems to be a very effective way of active protection of Iris sibirica and Trollius europaeus populations